A detachable design method of large-sized structure for heavy duty machine tool based on joint surface dynamics characteristic analysis. (July 2019) - Cheng, Qiang; Qi, Baobao; Liu, Zhifeng; Zhang, Guojun; Zhang, Caixia; Chen, Huaxiong
Heavy duty and ultra-heavy duty machine tools are used to manufacture large parts or super large parts in aerospace, ship, transportation, and energy industries. The weight of a structural part of ultra-heavy duty machine tools will reach more than 100 tons, because of which both manufacturing and transportation become very difficult. In this paper, a detachable design method for large-sized structures of heavy duty machine tools is presented. The proposed method aims to make large-sized structure into several detachable sections that can be bolted together in order to be casted and transported and remanufactured more easily. To analyze the influence of the joint surface, a three-dimensional fractal contact model based on the influence of domain expansion factor is used to identify stiffness and damping of the joint surface. On the basis of the analysis of the dependence of contact stiffness and damping of joint surface on dynamic characteristics of structural part, a detachable optimization model of a super span beam is established, and the particle swarm optimization algorithm is adopted to carry out the optimization. After that, the dynamic characteristics of the optimized design is analyzed and verified by finite element analysis. Based on the simulated verification, a detachable beam of heavy duty gantry machine was designed by the proposed method and verified by the field test. The illustration example shows that the large span beam can be detached into three sections that can be bolted together by high strength bolts, and it also has satisfied performance.